(untitled) (GEOMATE Journal, 2024)
In the analysis of reinforced concrete structures in general, and reinforced concrete road bridge structures in particular, using the limit state method with ultimate internal forces, according to the stress model, there are certain advantages compared to other previous methods. However, the limit state method with the stress model did not exhibit behavior close to the actual operation of the structure. In particular, the structural behavior of each working phase has not been described. Therefore, using the nonlinear analysis based on the nonlinear deformation model allows the description of the stress-strain state of the structure in any loading period, corresponding to the closer the actual behavior. This is a modern trend in many countries worldwide when applying this structural analysis model. This study was conducted based on the nonlinear deformation model in the technique codes of rules SP63.13330.2012, construction standards TCVN 5574:2018. In this study, a computational analysis was performed for reinforced concrete double-cantilever beams in road-bridge superstructures based on nonlinear deformational model to consider the nonlinear behavior of concrete and reinforcement. From the obtained results, we can clearly observe the effectiveness of the proposed method in evaluating the bearing capacity under a construction load. Therefore, the necessary conclusions and recommendations will be made for applying the nonlinear deformation model in analysis of this type of road-bridge superstructures.